Investigating affordability problems of utility services - a theoretical study on the ratio measure - Erik Gawel; Wolfgang Bretschneider (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
Unlike in developing countries, there tends to be no problem of access to water, electricity, and heating for private households in transition countries. However, transition countries have a considerable amount of low-income households, and the problem of affordability of these environmental-related utility services remains urgent. Welfare economics literature suggests to neglect affordability aspects by separating allocative from distributive impacts of pricing. In practice, this separation runs the risk of rendering impossible any sustainability-oriented price reform. An Institutional Economics approach takes competing objectives into account. From this viewpoint it appears to be worth investigating the affordability-concept. Although the affordability-related research has escalated remarkably in recent years, the theoretical contributions are still limited. Hence, we focus on the simple ratio measure often used in practice. We analyze the arguments speaking for the 'potential affordability approach'. But we find that - within that approach - adhering formally to the ratio measure is possible only under conditions that make no sense regarding the concern of the measure. Thus for most cases the ratio measure is misleading. Some considerations on practical use for governance conclude the paper.
Keywords: D11; H41; L97; O15; Q56; 330; Affordability; Transition Countries; Utility Services